Pelatihan Praktik Bimbingan Dan Konseling Perkembangan Bagi Guru Sekolah Dasar - Yosef Yosef; Fadhlina Rozzaqyah; Rahmi Sofah; Rani Mega Putri; Nur Wisma (STKIP Andi Matappa, 2022)
Developmental guidance and counseling practice training activities for elementary school teachers aim to improve the competence of elementary school teachers to integrate BK service practices in elementary schools both by elementary school teachers with BK and PGSD graduate degrees so that they can assist teachers in identifying and alleviating student problems through counseling strategies. This training was carried out from 22 September 2021 to 04 October 2021 for 41 elementary school teachers through three stages of training, namely the preparation, implementation and evaluation stages. The results of the training showed an increase in the positive perception of elementary school teachers and teachers' understanding of the implementation of counseling services in elementary schools from 63% to 100%.